Avaliação da força de união de diferentes técnicas de soldagem para uso em ortodontia - Henkin, Fernanda de Souza (2017)
Introduction: During orthodontic treatment, the use of appliances and devices that require welding procedures is often needed. Besides conventional silver soldering, different joining methods – with potentially higher biocompatibility – can be used. The mechanical strength of the welded areas is critical for their success, and must be evaluated. Objective: To review the joining methods for orthodontic purpose and evaluate the strength – by tensile strength measurements – of Silver Soldering, Spot, laser and TIG welding. Materials and Methods: 40 stainless steel wire segments with 0.8 mm diameter (Morelli, Sorocaba/SP, Brasil) were joined by means of silver soldering, spot, laser and TIG welding. For each joining method, 10 specimens were produced. Tensile strength test was performed 24 hours after welding by means of a universal testing machine (Instron Corporation, Canton, USA) using a cell load of 1000 N with a crosshead speed of 10 mm/minute. Results: The highest tensile strenght mean values was obtained by silver soldering (532.1N), followed by laser (419.8N), spot (301.1N) and TIG (216,3N) welding. Statistically significant diferences were observed between the groups, and the Dunn post-hoc test revealed difference between laser and spot welding (p=0046), laser and tig (p=0.016), spot and silver (p=2.5e-05) and silver and TIG (p=4.6e-06). Conclusions: The strenght of the laser joints are comparable to the Silver soldering joints, and represent a favorable alternative for orthodontic use. The spot and TIG welding methods presented comparable and significantly lower strenghts in relation do laser and silver soldering methods.